Pets - Reasoner, Charles (Greensboro : Rourke Publishing, 2011)
On die-cut board pages of varying sizes and shapes to represent pets.
A
Cover title
b
b
Keywords: Pets -- Texts; Board books; Toy and movable books -- Specimens